The Occurrence of Intersex in Different Populations of the Marine Amphipod Echinogammarus marinus in North-West Brittany – A Longterm-Study - Oetken, Matthias; Adler, Marissa; Alt, Katharina; Bachmann, Jean; Dombrowski, Andrea; Duhme, Franziska; Gabriel, Anna-Louise; Grünewald, Judith; Jourdan, Jonas; Lück, Maren; Mensch, Carola; Rösch, Dominik; et al. (Frontiers in Endocrinology, 2021)
In the past two decades, an increasing body of studies has been published on the intersex phenomenon in separate-sexed crustaceans from marine and freshwater ecosystems. Various causes are being considered that could have an influence on the occurrence of intersex. Besides genetic factors, environmental conditions such as photoperiodicity, temperature, salinity and parasitism, but also environmental pollution with endocrine disrupting chemicals (EDCs) are discussed. As part of a long-term monitoring (2012 - 2020) in north-west Brittany, we recorded the occurrence of intersex in the marine amphipod Echinogammarus marinus. We quantified the intersex incidence at marine and estuarine sites and analyzed the incidence in relation to the endocrine potential of the sediments. Intersex occurred with mean frequencies between 0.87% and 12%. It was striking that the incidence of intersex increased with increasing distance from the sea. Since the highest incidence was observed at the range boundary of this stenohaline species, we assume that intersex is triggered by endocrine potential and increasing stress due to increasing freshwater content − and thus an interplay of different environmental factors.